EDUKASI PEMANFAATAN TANAMAN KELOR DALAM UPAYA PENCEGAHAN HIPERTENSI PADA KADER POSYANDU - Wahyuni, Wahyuni; Nooratri, Erika Dewi; Fatmawati, Siti; Santika, Aprilia Puteri (P3M Universitas Aisyiyah Surakarta, 2025)
The World Health Organization (WHO) estimates that 1.13 billion people worldwide suffer from hypertension, most of whom (two-thirds) live in low- and middle-income countries. In 2015, 1 in 4 men and 1 in 5 women experienced hypertension WHO. One way to overcome hypertension is by utilizing moringa leaves. Moringa leaves are widely planted by farmers in Sidorejo but not many people know about their use, therefore community service will be carried out by providing education to posyandu cadres. the method used in this activity is the lecture method, question and answer, and demonstration of making various moringa leaf preparations for preventing hypertension. the results of this activity are that after education related to the material on the benefits of moringa leaves for preventing hypertension, the results previously showed that those who knew about the definition of hypertension were 22 (73.3%) after education became 30 (100%) an increase of 26.7%, while the highest increase was achieved in the material on food variations from moringa leaves which previously only 7 people (23.3%) became 27 people (90%) an increase of 66.7%. Cadres can increase their knowledge regarding the prevention of hypertension with Moringa plants and cadres can make various processed products from Moringa to prevent hypertension.